Study of influences of rock hardness on crack evolution rule under hydraulic fracturing. Issue 3 (August 2020) - Liu, Jialiang; Liu, Yonghao; Zhu, Yujie; Zhou, Dongping; He, Hua; Zhou, Junjie; Wang, Kai
Abstract: In order to study the crack evolution rules of hydraulic fracturing rock with different hardness, a numerical model of hydraulic fracturing rock was established. It explored the expansion length, expansion width, propagation rate of crack and initiation pressure of hydraulic fracturing different hardness rocks. The results show that the expansion length, the propagation rate along length and the initiation pressure of crack were positively correlated with the rock hardness, and the expansion width and propagation rate along width were negatively correlated with the rock hardness. In addition, considering the effect of in-situ stress difference, it took granite as an example, and studied the effect of in-situ stress difference on crack propagation. It is found that as the in-situ stress difference increases, the initiation pressure of the crack decreases, and the crack expansion length and the propagation rate along length shows a linear increase, but it has little effect on the crack expansion width. The results can provide theoretical references for improving the application of hydraulic fracturing technology in hard rock excavation, such as the coal roadway excavation, the tunnel excavation and so on.